Konsep Perlindungan Anak dalam Fiqh Hadlanah dan UU No. 23 Tahun 2002 J.O UU No. 35 Tahun 2014 - Anam, Mohamad Hoirul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2020)
Children are assets of the future, the progress of a civilization depends on the next generation. Children are a trust and a gift from God Almighty, the owner of life on earth, and the One who is everlasting and deadly. Therefore the existence of a child must always be safeguarded and protected by his dignity and dignity as humans do in general. Both Religion and the State command that to protect and protect the child until he is able to stand firm and independent. Parents' obligations to children are caring, raising and marrying. The formal rules of legality are listed in Law No. 35 of 2014 which is an update of Law No. 23 of 2002. The two Law Products (Religion and the State) mutually reinforce children's rights with the aim that children can grow and develop into a human being who is reliable, has the effect and is able to stand alone